Dominasi Penjualan Offline dalam Era Digital: Studi Kualitatif pada Getuk Goreng Sokaraja Haji Tohirin - Muhammad Jaisy Abimanyu; Kurnia Tri Yunanto; Indrawan Firdauzi (Lingka Ekonomika, 2025)
This study aims to analyze the dominance of offline sales in the digital era through a case study of Getuk Goreng Sokaraja Haji Tohirin. Despite the rapid growth of digitalization, offline sales among MSMEs remain crucial for maintaining direct relationships with consumers. Using a qualitative approach through in-depth interviews and questionnaires with business owners and consumers, the findings reveal that authentic shopping experiences, face-to-face interactions, and trust in product quality are the main factors influencing consumers to shop offline. While digital platforms offer convenience, social experiences and emotional closeness remain irreplaceable. The main challenges faced by MSMEs in adopting digitalization include limited resources and high shipping costs. Therefore, this study suggests a gradual adoption of digital technologies and enhanced digital training to enable MSMEs to optimize both offline and online sales through a hybrid strategy.